PERBEDAAN BERMAKNA KADAR SERUM AMILOID A ANTARA STENOSIS KORONER DIBANDINGKAN BUKAN STENOSIS KORONER (Significantly Higher Level of Serum Amyloid A Among Coronary Stenosis Compared to NonStenosis) - I Nyoman G Sudana; Setyawati Setyawati; Usi Sukorini (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2015)
Coronary stenosis is one of the major causes of death from heart disease. The gold standard of coronary stenosis diagnosis isestablished with angiography, however it is invasively, complicated and expensive. Serum Amyloid A (SAA) is an acute phase proteinthat appears as chronic and acute inflammatory agent that is specific to the process of stenosis development. Serum Amyloidal A testmethod is noninvasive, relatively easy and affordable. The aim of this study was to know the differences of Serum Amyloid A levelsin patients with nonstenosis and coronary stenosis in Dr. Sardjito General Hospital Yogyakarta by determination. The study is a casecontrol study. The samples were selected consecutively with typical chest pain, were divided into two (2) groups of nonstenosis andstenosis by coronary angiography test. The principal of the Serum Amyloid A test is ELISA method. Nonstenosis and coronary stenosisgroups were analyzed by mean of Serum Amyloid A level based on the angiography test. The data were analyzed with Independentt-test, odds ratio with a significancy of p <0.05 and confidence interval 95%. The samples of this study consisted of 60 patients, dividedinto nonstenosis and coronary stenosis. The analysis of Independent t tests showed significant differences between the subject SAA levelsof nonstenosis and stenosis (4.35 ug/mL vs 21.75 mg/mL, p=0.001, with an odds ratio 9.84 (CI 95% 2.38 to 40.73). Based on thisstudy, it can be conclued that the results indicate significantly higher level of Amyloid A Serum among the coronary stenosis comparedto the nonstenosis.